ANALISIS NILAI KARAKTER RELIGIUS DAN PEDULI SOSIAL PADA PEMBELAJARAN PKN KURIKULUM MERDEKA KELAS IV DI SDN KERTAUNGARAN - Tedi Hermansyah; Oman Suryaman (STKIP Subang, 2024)
This research aims to find out the values ​​of religious character and social care in PKN learning in class IV of the independent curriculum. The benefit of this research is as a source of information for teachers and researchers. This research is based on the results of observations regarding the value of religious character and social care which is good even though there are some students whose religious character and social care have not yet been formed. The sources or informants in this research were the principal, class IV teacher and three class IV students at SDN Kertaungan. This type of research uses descriptive qualitative methods. Technique Data collection is by interview observation and documentation. Data analysis was carried out by data reduction, data presentation, data verification and conclusions. The results of this research show that the application of religious values ​​and social care has been well established. This is supported by effective refraction or learning, good facilities, the presence of religious posters, anti-bullying posters. Independent curriculum PKN learning in class IV can integrate religious values ​​and social care contained in the book. So that it can improve and develop religious attitudes and social care in class IV at SDN Kertaungaran